Advances in Metal Artifact Reduction Techniques for Periprosthetic Soft Tissue Imaging - Ariyanayagam, Timothy; Malcolm, Paul Napier; Toms, Andoni Paul (Seminars in Musculoskeletal Radiology, 2015)
Artifact from metallic orthopedic prosthesis is caused by inhomogeneity in the B0 magnetic field, particularly in the frequency encoding direction. This results in signal voids, signal pileup, and geometric distortion. Advances in reducing this artifact allow us to assess the complications of joint replacement and improve imaging of nearby tissues such as within the pelvis. Selection of titanium implants and lower field strength MR units provide optimal conditions for artifact reduction. Conventional sequences can be optimized by using inversion recovery sequences, large matrices, high receiver bandwidths, and thin slices. Optimizing these parameters comes with a penalty in terms of signal-to-noise ratio or increased acquisition times. Successful artifact reduction depends on the strength of the frequency encoding gradients. Newer dedicated artifact reduction sequences include view-angle-tilting and a selection of multispectral techniques including multiacquisition variable-resonance image combination (MAVRIC) and slice encoding for metal artifact correction (SEMAC). Many of these are being used in combination. The multispectral sequences acquire three-dimensional data at very narrow frequencies and use of phase encoding for spatial localization. Planar images can then be reconstructed with very little susceptibility artifact.
Keywords: susceptibility artifact; orthopedic prosthesis; artifact reduction